Trajectory Tracking and Control of Differential Drive Robot for Predefined Regular Geometrical Path. (2016) - Mathew, Robins; Hiremath, Somashekhar S.
Abstract: Trajectories made by concatenating straight motion and in place turning primitive are one that can be easily followed by a differential drive robot. This paper presents trajectory tracking and control of differential drive robots along a predefined regular geometrical path made up of these primitives. A control algorithm was developed to control the robot along different trajectories. The algorithm takes user input from a user interface through which one can select the type of trajectory, dimensions of the trajectory and tracking velocity. Simulations were carried out to obtain the trajectory tracked by the robot using commercial available software MATLAB, Release 2010. Experiments were conducted for tracking regular trajectories such as Triangular, Rectangular and Square and these experimental results were found to be in good agreement with the simulation results.